Optimized arc optics for the HE-LHC - Nosochkov, YM; Cai, Y; Crouch, MP; Giovannozzi, M; Hofer, M; Keintzel, J; Risselada, T; Todesco, E; Tomás, R; Tomás, R; Van Riesen-Haupt, L (Joint Accelerator Conferences Website, 2018)
The High Energy LHC (HE-LHC) proton-proton collider is a proposed replacement of the LHC in the existing 27-km tunnel, with the goal of reaching the centre-of-mass beam energy of 27 TeV. The required higher dipole field can be realized by using 16-T dipoles being developed for the FCC-hh design. A major concern is the dynamic aperture at injection energy due to degraded field quality of the new dipole based on Nb3Sn superconductor, the potentially large energy swing between injection and collision, and the slightly reduced magnet aperture. Another issue is the field in quadrupoles and sextupoles at top energy, for which it may be cost-effective, wherever possible, to stay with Nb-Ti technology. In this study, we explore design options differed by arc lattice, for three choices of injection energy, with the goal of attaining acceptable magnet field and maximum injection dynamic aperture with dipole non-linear field errors.